2020
DOI: 10.1186/s12960-020-00516-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Medical Doctors Global Health and Tropical Medicine on decision-making in caesarean section: a pre- and post-implementation study in a rural hospital in Malawi

Abstract: Background Medical doctors with postgraduate training in Global Health and Tropical Medicine (MDGHTM) from the Netherlands, a high-income country with a relatively low caesarean section rate, assist associate clinicians in low-income countries regarding decision-making during labour. Objective of this study was to assess impact of the presence of MDGHTMs in a rural Malawian hospital on caesarean section rate and indications. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
0
8
0
3
Order By: Relevance
“…The 133 included studies collectively reported on more than 9.1 million surgical procedures (median per study, 894 [IQR, 97-4259]) and more than 11.4 million participants (median per study, 989 [IQR, 257-6857]) from 63 LMICs . Of all 133 LMICs, we found studies from 15 of all 29 low-income countries (51.7%), 25 of all 50 lower-middle–income countries (50.0%), and 23 of all 55 upper-middle–income countries (41.8%) . Fourteen studies (10.5%) were multinational …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 133 included studies collectively reported on more than 9.1 million surgical procedures (median per study, 894 [IQR, 97-4259]) and more than 11.4 million participants (median per study, 989 [IQR, 257-6857]) from 63 LMICs . Of all 133 LMICs, we found studies from 15 of all 29 low-income countries (51.7%), 25 of all 50 lower-middle–income countries (50.0%), and 23 of all 55 upper-middle–income countries (41.8%) . Fourteen studies (10.5%) were multinational …”
Section: Resultsmentioning
confidence: 99%
“…Most studies (115 [86.5%]) were published in 2010 or after, with a marked increase in the number of included studies per year. Most articles were written in English (126 [94.7%]) . Health care settings were hospital based or secondary care in 93 studies (69.9%) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A dataset with all births occurring during the two-year study period, as used in a previous publication, was adapted for detailed analysis of women with prolonged second stage of labour. 12 St. Luke's hospital is a 150-bed faith-based facility in rural Southern Malawi, providing free Basic and Comprehensive Emergency Obstetric Care for its catchment population.…”
Section: Study Design and Settingmentioning
confidence: 99%